Cost–effectiveness of rituximab in follicular lymphoma. (October 2012) - Johnston, Karissa M; Bolbocean, Corneliu; Connors, Joseph; Peacock, Stuart
In advanced follicular lymphoma, rituximab is currently used with chemotherapy as induction therapy, and as maintenance monotherapy following induction in previously untreated patients and treatment-experienced relapsed/refractory patients. Herein, the authors characterize the clinical effectiveness, safety and cost–effectiveness of rituximab in follicular lymphoma, based on the literature review. Rituximab has a favorable safety profile and has been shown to improve progression-free survival, with some evidence of improvements to overall survival, particularly for relapsed/refractory patients. Rituximab has consistently been found to have a favorable economic profile, with cost per quality-adjusted life year falling within standard thresholds for cost–effectiveness. Challenges in cost–effectiveness analysis include the fact that life expectancy for patients with follicular lymphoma exceeds the period of available follow-up data and that treatment pathways are more complex than the model structures frequently used in oncology models. As data accrue and more complex models are developed, the cost–effectiveness of rituximab can be more accurately assessed.